Method for displaying grain boundary of high-chromium-nickel multi-component alloying austenitic heat-resistant steel

By using FeCl3+HCl aqueous solution and optimized grinding and polishing process, the grain boundary corrosion problem of high-chromium nickel multi-alloy austenite heat-resistant steel is solved, and the high-efficiency corrosion effect without electrolytic corrosion is achieved. It is suitable for the development of steel for ultra-supercritical units. Microtissue analysis.

CN119269206APending Publication Date: 2025-01-07ANHUI METALLURGICAL TECH VOCATIONAL COLLEGE

Patent Information

Application Number
CN202411412996.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The prior art is difficult to effectively corrode the grain boundaries of high-chromium nickel multi-alloyed austenite heat-resistant steel, which usually requires electrolytic erosion and complex operation, and the traditional erosion liquid has poor effect.

Method used

The FeCl3+HCl room temperature aqueous solution is used as the corrosion agent to control the concentration of FeCl3 and HCl, and combine the grinding and polishing processes to achieve grain boundary corrosion without electrolytic erosion, simplifying operation.

Benefits of technology

It has achieved effective corrosion on the grain boundaries of high-chromium nickel multi-alloyed austenite heat-resistant steel, with simple operation and good microstructure analysis effect, and is suitable for steel for ultra-supercritical units.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119269206A_ABST
    Figure CN119269206A_ABST
Patent Text Reader

Abstract

The invention discloses a display method of a high-chromium-nickel multi-component alloying austenitic heat-resistant steel grain boundary, and belongs to the technical field of metallographic sample preparation. The method comprises the following steps: grinding and polishing a to-be-corroded high-chromium-nickel multi-element alloying austenitic heat-resistant steel sample; enabling the ground and polished surface to be corroded of the sample to be in full contact with a corrosive agent for 2.5-4 minutes so as to corrode the sample; wherein the corrosive agent is a normal-temperature aqueous solution of FeCl3 and HCl, the mass concentration of FeCl3 in the corrosive agent solution is 4.8-5.2%, and the volume concentration of HCl is 20%; and washing the corroded sample with clear water, then washing with absolute ethyl alcohol, and drying. According to the method, the grain boundary corrosion of the high-chromium-nickel multi-element alloying heat-resistant steel for the ultra-supercritical unit can be realized at normal temperature, electrolytic corrosion is not needed, the operation is relatively simple, and the components of the corrosive agent are also relatively simple.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metallographic sample preparation, and in particular relates to a method for displaying austenite grain boundaries of high-chromium-nickel multi-element alloyed heat-resistant steel for ultra-supercritical units with high alloy content, strong corrosion resistance and good oxidation resistance. Background Art

[0002] Increasing boiler steam temperature and pressure and developing ultra-supercritical units are effective means to improve coal-fired power generation efficiency and reduce harmful gas emissions. The increase in steam parameters has put forward higher requirements on the materials used for boiler high-temperature components. Austenitic heat-resistant steel is widely used in ultra-supercritical units due to its excellent oxidation resistance, corrosion resistance and high-temperature endurance strength. With the increase in steam parameters, the composition design of austenitic heat-resistant steel must further increase the content of Cr and Ni elements, and reasonably match W, Co, Cu, Mo, Nb, N and other elements to form a multi-component composite strengthening mechanism of solid solution strengthening and dispersed precipitation phase precipitation strengthening. The total alloy content exceeds 50% to improve the material's high-temperature strength and high-temperature structural stability.

[0003] However, high content of alloying elements will lead to a series of processing difficulties, causing serious solidification segregation and precipitation, which will have a serious impact on hot deformation processing, deteriorate the hot processing performance of steel, increase the high temperature deformation resistance, narrow hot processing temperature range, and cause serious hot processing cracking and mixed crystal phenomena. Therefore, studying the evolution law of hot processing microstructure of high chromium and nickel multi-element alloyed austenitic heat-resistant steel is of great significance to the formulation of its hot processing process parameters, and it is very important to explore a simple and effective method to display the austenite grain boundary of high chromium and nickel multi-element alloyed heat-resistant steel.

[0004] At present, there are many patent documents reporting on the corrosion method of the original austenite grain boundary of ferrite or martensitic heat-resistant steel, such as "A method for displaying the original austenite grain boundary of steel for Co-containing ultra-supercritical units" (publication number CN105547795 A), "A corrosive agent and display method for displaying the original austenite grain boundary of heat-resistant steel" (publication number CN109187152 A), "A corrosive agent for displaying the original austenite grain boundary of 9% Cr steel and its application" (publication number CN102517586 A), "A method for displaying the original austenite grain boundary of martensitic heat-resistant steel" (CN103398892 A), "A method for displaying the original austenite grain boundary of P91 and P92 steels" (CN 102590050 A), etc. There are relatively few patent documents on the display of grain boundaries of austenitic heat-resistant steel. Among them, "An etchant for displaying fine-grained austenitic stainless steel grain boundaries and its preparation method" (CN102888608 A) discloses an etchant for displaying grain boundaries of austenitic stainless steel, but the configuration process of the etchant in the patent is complicated, the etchant method has cumbersome procedures, the etchant effect is average, and it is not suitable for high-chromium-nickel multi-alloyed austenitic heat-resistant steel. At present, most austenitic heat-resistant steels are electrolytically etched with oxalic acid solution or nitric acid alcohol solution. The etchant effect of traditional etchant is not good, and the electrolytic etchant operation is relatively complicated. Summary of the invention

[0005] The purpose of the present invention is to provide a method for displaying the grain boundaries of high-chromium-nickel multi-element alloyed austenitic heat-resistant steel, so as to solve the problem in the prior art that it is difficult to corrode the grain boundaries of austenitic heat-resistant steel and electrolytic corrosion is usually required. The present invention does not require electrolytic corrosion or water bath heating, and its operation is simple and effective, and the corrosion effect is good. It has an important improvement effect and practical significance on the analysis of the thermal deformation microstructure of materials.

[0006] In order to achieve the above object, the technical solution provided by the present invention is:

[0007] The present invention provides a method for displaying grain boundaries of high-chromium-nickel multi-element alloyed austenitic heat-resistant steel, comprising:

[0008] Grinding and polishing the high chromium-nickel multi-element alloyed austenitic heat-resistant steel sample to be corroded;

[0009] The sample surface to be corroded after grinding and polishing is fully contacted with the corrosive agent for 2.5 to 4 minutes to corrode the sample; wherein the corrosive agent is a normal temperature aqueous solution of FeCl3+HCl, the mass concentration of FeCl3 in the corrosive solution is 4.8 to 5.2%, preferably 5g / 100ml of the corrosive solution, and the volume concentration of HCl is 20%;

[0010] The corroded specimens were first rinsed with clean water, then rinsed with anhydrous ethanol and blown dry. The air outlet direction during the drying process was perpendicular to the spraying direction of the anhydrous ethanol.

[0011] The high chromium-nickel multi-element alloyed austenitic heat-resistant steel comprises the following alloy components in percentage by mass: C: 0.03-0.08, Cr: 18.0-25.0, Ni: 21.5-31.0.

[0012] Due to the alloy content of high chromium-nickel multi-alloyed austenitic heat-resistant steel, especially the high Cr and Ni content, it is difficult to effectively corrode its austenite grain boundaries. Therefore, electrolytic corrosion is usually required in the experimental process, and the operation is relatively complicated. In view of the above situation, the present invention adopts FeCl3+HCl room temperature aqueous solution as a corrosive agent, and effectively controls the concentrations of FeCl3 and HCl, so that the grain boundaries of high chromium-nickel austenitic heat-resistant steel can be effectively corroded, and no heating and electrolysis are required. The operation is relatively simple, which is convenient for analyzing the thermal deformation microstructure of high chromium-nickel multi-alloyed austenitic heat-resistant steel in the laboratory. If the concentration of the corrosive solution is improperly controlled, two situations will occur: one is that the concentration is too low, the clarity of the grain boundary corrosion is poor, and the corrosion time is increased or difficult to accurately judge; the other is that the concentration is too high, the clarity of the grain boundary corrosion is poor, black spots will appear around some grain boundaries, and the corrosion time will be shortened or difficult to accurately judge.

[0013] Furthermore, the high chromium-nickel multi-element alloyed austenitic heat-resistant steel also includes the following alloy components in percentage by mass: Si: ≤0.50; Mn: ≤0.50; Co: 1.0~4.0; Mo: ≤0.40; Nb: 0.3~0.65; N: 0.15~0.30; Co: 1.0~4.0; Cu: 2.0~4.0; B: 0.002~0.008.

[0014] Furthermore, the high chromium-nickel multi-element alloyed austenitic heat-resistant steel sample to be corroded is ground, including: grinding on 240#, 400#, 600#, 800#, 1000#, 1200#, 1500# and 2000# coarse sandpaper in sequence, then grinding on 2000# fine sandpaper, and finally grinding on 4000# water sandpaper.

[0015] Furthermore, each time a new grit sandpaper is replaced during the grinding process, the sample is rotated 90 degrees along the grinding surface.

[0016] Furthermore, the high chromium-nickel multi-element alloyed austenitic heat-resistant steel sample to be corroded is polished by using a polishing cloth made of pressure-sensitive felt. The polishing paste used on the polishing cloth is diamond grinding paste with a particle size of W2.5.

[0017] Furthermore, after the sample is polished, the polished surface is rinsed with anhydrous ethanol and blown dry. The air outlet direction during the drying is perpendicular to the spraying direction of the anhydrous ethanol. If the spraying direction of the alcohol is consistent with the air outlet direction of the hair dryer, watermarks are easily generated on the surface of the sample, resulting in unclear grain boundaries and affecting experimental observations.

[0018] Furthermore, the grinding and polishing of the sample to be corroded surface is fully contacted with the corrosive agent for 2.5 to 4 minutes, specifically: clamp the sample with tweezers, make the sample to be corroded face up and immerse it completely in the corrosive agent. The control of the corrosion time is conducive to ensuring the corrosion effect. If the corrosion time is short, the grain boundary corrosion is not obvious. If the corrosion time is too long, over-corrosion is likely to occur.

[0019] Furthermore, it also includes: placing the corroded sample on an optical microscope for preliminary observation. If there are obvious scratches, black spots, etc. on the grain boundaries, use 600# sandpaper to grind the corroded surface of the sample in the opposite direction of the black spots or scratches, and then grind it on 4000# water sandpaper, and finally repeat the polishing and corrosion operations, so as to effectively eliminate the influence of black spots and scratches.

[0020] Furthermore, before grinding the sample, it is first placed in an alcohol solution for ultrasonic cleaning.

[0021] In summary, the technical solution provided by the present invention can achieve the following beneficial effects compared with the prior art:

[0022] (1) The present invention adopts FeCl3+HCl aqueous solution as the corrosive agent and optimizes and controls the concentrations of FeCl3 and HCl, so that the intergranular corrosion of high chromium-nickel multi-element alloyed heat-resistant steel for ultra-supercritical units can be achieved at room temperature without electrolytic corrosion. The operation is relatively simple and the components of the corrosive agent are also relatively simple.

[0023] (2) The present invention further optimizes the grinding and polishing process before etching, which is conducive to further improving the etching effect of the subsequent stage and preventing the presence of obvious black spots, scratches, etc. from affecting the grain boundary display. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1-Figure 5 They are respectively microscopic pictures of austenite grain boundaries of high chromium-nickel multi-element alloyed heat-resistant steel for ultra-supercritical units in the embodiments under different deformation states. DETAILED DESCRIPTION

[0025] The present invention uses a normal temperature FeCl3+HCl aqueous solution as a corrosive solution, wherein the mass concentration of FeCl3 in the corrosive solution is 4.8-5.2%, and the volume concentration of HCl is 20%. The corrosive solution can be effectively applied to high chromium-nickel multi-element alloyed heat-resistant steel for ultra-supercritical units, and the overall process operation is simple, and no heating or electrolytic corrosion is required. The alloy composition of the high chromium-nickel multi-element alloyed heat-resistant steel contains C: 0.03-0.08 by mass percentage; Si: ≤0.50; Mn: ≤0.50; Co: 1.0~4.0; P: ≤0.020; S: ≤0.010; Cr: 18.0~25.0; Mo: ≤0.40; Nb: 0.3~0.65; N: 0.15~0.30; Ni: 21.5~31.0; Co: 1.0~4.0; Cu: 2.0~4.0; Al≤0.40; B: 0.002~0.008; Fe: balance

[0026] In order to further understand the content of the present invention, the present invention is now described in detail in conjunction with specific embodiments.

[0027] Example

[0028] A method for displaying grain boundaries of high chromium-nickel multi-element alloyed austenitic heat-resistant steel in this embodiment includes:

[0029] 1. Preparation, grinding and polishing of samples

[0030] ① Preparation: Φ8mm×15mm cylindrical specimens were cut from the steel plate by wire cutting, and hot compression deformation experiments were carried out at different deformation temperatures and strain rates.

[0031] ② Grinding and polishing

[0032] Firstly, the isothermal hot compression test specimens processed under different deformation conditions were placed in an alcohol solution and cleaned with an ultrasonic cleaner to remove the oil and dirt on the surface for 5 minutes, and then dried with a hair dryer.

[0033] Then grind on 240#, 400#, 600#, 800#, 1000#, 1200#, 1500# and 2000# coarse sandpaper, 2000# fine sandpaper and 4000# water sandpaper in turn, and use tap water as lubricant during the water sandpaper grinding process. Each time a new grit sandpaper is replaced during the above grinding process, the sample needs to be rotated 90 degrees along the grinding surface.

[0034] Finally, the sample was polished on a polishing cloth made of pressure-sensitive adhesive material with a diameter of 200 mm. The polishing paste used on the polishing cloth was a diamond grinding paste with a particle size of W2.5. The sample was polished until the interface was smooth, without scratches or stains, and then the polished surface was rinsed with alcohol and blown dry.

[0035] 2. Preparation of corrosive agent and chemical corrosion of samples

[0036] ① Preparation of the etching solution: First, clean the equipment needed for the preparation of the etching solution with alcohol and blow dry; weigh 5g FeCl3 on the electronic scale, and use a measuring cylinder and a rubber-tipped dropper to measure 20ml of concentrated HCl; then put the solid FeCl3 into a 300ml beaker, then pour HCl into the beaker, and stir continuously with a glass rod until the FeCl3 solid is completely dissolved, then add deionized water to 100ml on the beaker scale, and stir the solution evenly with a glass rod. Finally, let it stand for about 1 minute to obtain a etching solution with a content of about 5% ferric chloride (concentration 5g / 100ml etching solution).

[0037] ②Corrosion: Hold the ground sample with tweezers, with the ground surface facing up, immerse it in the corrosive agent, let it stand for about 200 seconds, take out the sample, rinse it with clean water first, then rinse it with alcohol solution, and blow it dry. The direction of the air outlet should be perpendicular to the spraying direction of the alcohol solution.

[0038] 3. Grain boundary observation

[0039] The corroded sample is first placed on an optical microscope for preliminary observation. If there are obvious scratches, black spots, etc. on the grain boundary, the corroded surface of the sample is polished in the opposite direction of the black spots or scratches with 600# sandpaper. Then the prepared experimental sample is observed under a metallographic microscope for microstructure under different deformation conditions.

[0040] Specifically, in this embodiment, the steel sample for ultra-supercritical unit is heated to 1250°C, kept at this temperature for 3 minutes, and immediately water quenched. Then, the grain boundary structure thereof is studied by the grain boundary display method of this embodiment. The metallographic photograph thereof is shown in FIG. Figure 1 shown.

[0041] Example 2

[0042] In this embodiment, the steel sample for ultra-supercritical unit is heated to 1250°C, kept at this temperature for 3 minutes, and then cooled to 950°C and heated for 10 seconds. -1 The strain rate was used for compression deformation, the deformation amount was 60% of the engineering strain, and the deformation was immediately quenched. Then the grain boundary changes were studied. The metallographic photos are shown in Figure 2 shown.

[0043] Example 3

[0044] In this embodiment, the steel sample for ultra-supercritical unit is heated to 1250℃, kept at this temperature for 3 minutes, and then cooled to 1100℃. -1 The strain rate was used for compression deformation, the deformation amount was 60% of the engineering strain, and the deformation was immediately quenched. Then the grain boundary changes were studied. The metallographic photos are shown in Figure 3 shown.

[0045] Example 4

[0046] In this embodiment, the steel sample for ultra-supercritical unit is heated to 1250°C, kept at this temperature for 3 minutes, and then cooled to 1150°C. -1 The strain rate was used for compression deformation, the deformation amount was 60% of the engineering strain, and the deformation was immediately quenched in water. Then the grain boundary changes were studied. The metallographic photos are shown in Figure 4 shown.

[0047] Example 5

[0048] In this embodiment, the steel sample for ultra-supercritical unit is heated to 1250°C, kept at this temperature for 3 minutes, and then cooled to 1150°C. -1 The strain rate was used for compression deformation, the deformation amount was 60% of the engineering strain, and the deformation was immediately quenched in water. Then the grain boundary changes were studied. The metallographic photos are shown in Figure 5 shown.

[0049] It can be seen from Examples 1-5 that the method of the present invention can achieve effective corrosion of the grain boundaries of high chromium-nickel multi-alloyed austenitic heat-resistant steel, the composition of the etching solution is simple, and the overall corrosion operation is simple, so it is convenient to study the austenite grain conditions of ultra-supercritical unit steel under different deformation conditions.

Claims

1. A method for displaying grain boundaries of high chromium-nickel multi-element alloyed austenitic heat-resistant steel, characterized in that: include: Grinding and polishing the high chromium-nickel multi-element alloyed austenitic heat-resistant steel sample to be corroded; The sample surface to be corroded after grinding and polishing is fully contacted with the corrosive agent for 2.5 to 4 minutes to corrode the sample; wherein the corrosive agent is a normal temperature aqueous solution of FeCl3+HCl, the mass concentration of FeCl3 in the corrosive solution is 4.8 to 5.2%, and the volume concentration of HCl is 20%; The corroded specimens were first rinsed with clean water, then rinsed with anhydrous ethanol and blown dry. The air outlet direction during the drying process was perpendicular to the spraying direction of anhydrous ethanol. The high chromium-nickel multi-element alloyed austenitic heat-resistant steel comprises the following alloy components in percentage by mass: C: 0.03-0.08, Cr: 18.0-25.0, Ni: 21.5-31.

0.

2. The method for displaying grain boundaries of high chromium-nickel multi-element alloyed austenitic heat-resistant steel according to claim 1, characterized in that: The high chromium-nickel multi-element alloyed austenitic heat-resistant steel also includes the following alloy components in mass percentage: Si: ≤0.50; Mn: ≤0.50; Co: 1.0-4.0; Mo: ≤0.40; Nb: 0.3-0.65; N:0.15~0.30; Co: 1.0~4.0; Cu: 2.0~4.0; Al≤0.40; B:0.002~0.008。 3. The method for displaying grain boundaries of high chromium-nickel multi-element alloyed austenitic heat-resistant steel according to claim 2, characterized in that: The method of grinding the high chromium-nickel multi-element alloyed austenitic heat-resistant steel sample to be corroded includes: grinding on 240#, 400#, 600#, 800#, 1000#, 1200#, 1500# and 2000# coarse sandpaper in sequence, then grinding on 2000# fine sandpaper, and finally grinding on 4000# water sandpaper.

4. The method for displaying grain boundaries of high chromium-nickel multi-element alloyed austenitic heat-resistant steel according to claim 3, characterized in that: Each time a new grit sandpaper is replaced during the grinding process, the sample is rotated 90 degrees along the grinding surface.

5. The method for displaying grain boundaries of high chromium-nickel multi-element alloyed austenitic heat-resistant steel according to claim 2, characterized in that: The high chromium-nickel multi-element alloyed austenitic heat-resistant steel sample to be corroded is polished, specifically, the sample is polished with a polishing cloth made of pressure-sensitive felt, and the polishing paste used on the polishing cloth is a diamond grinding paste with a particle size of W2.

5.

6. The method for displaying grain boundaries of high chromium-nickel multi-element alloyed austenitic heat-resistant steel according to claim 5, characterized in that: After the sample is polished, the polished surface is rinsed with anhydrous ethanol and blown dry. The direction of the air outlet during drying is perpendicular to the spraying direction of the anhydrous ethanol.

7. The method for displaying grain boundaries of high chromium-nickel multi-element alloyed austenitic heat-resistant steel according to any one of claims 1 to 6, characterized in that: The method of allowing the ground and polished surface of the sample to be corroded to be fully in contact with the corrosive agent for 2.5 to 4 minutes specifically comprises: clamping the sample with tweezers, making the surface of the sample to be corroded face upward and completely immersing the sample in the corrosive agent.

8. The method for displaying grain boundaries of high chromium-nickel multi-element alloyed austenitic heat-resistant steel according to any one of claims 1 to 6, characterized in that: Also includes: The corroded sample was first placed on an optical microscope for preliminary observation. If there were obvious scratches, black spots, etc. on the grain boundaries, the corroded surface of the sample was polished in the opposite direction of the black spots or scratches using 600# sandpaper, and then ground on 4000# water sandpaper, and finally the polishing and corrosion operations were repeated.

9. The method for displaying grain boundaries of high chromium-nickel multi-element alloyed austenitic heat-resistant steel according to any one of claims 1 to 6, characterized in that: Before grinding, the specimens were ultrasonically cleaned in an alcohol solution.

Citation Information

Patent Citations

  • Corrosive agent for displaying 9% Cr steel original austenite grain boundary and application thereof

    CN102517586A

  • Method for displaying P91 and P92 steel original austenite grain boundaries

    CN102590050A

  • Corrosive for displaying austenitic stainless steel grain boundary of fine grains and method for preparing corrosive

    CN102888608A

  • Method for displaying prior austenite crystal boundary of martensite heat-resistant steel

    CN103398892A

  • Display method of original austenite crystal boundary of steel for making Co containing type ultra-supercritical set

    CN105547795A

Cited By

  • Iron-nickel-based heat-resistant alloy and grain size display method thereof

    CN121612664A